Business architecture management : architecting the business for consistency and alignment - Simon, Daniel; Schmidt, Christian (Management for Professionals,, 2015)
This book presents a comprehensive overview of enterprise architecture management with a specific focus on the business aspects. While recent approaches to enterprise architecture management have dealt mainly with aspects of information technology, this book covers all areas of business architecture from business motivation and models to business execution. The book provides examples of how architectural thinking can be applied in these areas, thus combining different perspectives into a consistent whole. In-depth experiences from end-user organizations help readers to understand the abstract concepts of business architecture management and to form blueprints for their own professional approach. Business architecture professionals, researchers, and others working in the field of strategic business management will benefit from this comprehensive volume and its hands-on examples of successful business architecture management practices.